PERSPECTIVE REINFORCING MATERIAL FOR FIBRE CONCRETE - A. V. Vedeneev; О. I. Ignatenko; V. I. Gritsaenko (Литьë и металлургия)
The different types of wire fiber are considered, advantages of fiber of high-modular wire with heightened bending stiffness are shown. analysis by volumes of fiber production in the world is carried out. Peculiarities of fiber production at RUP «BMZ» are shown. recommendations on correlation «wire diameter-fiber length» are given for different types of fiber for prevention of fiber caking at production of fibrous concrete are given.